Combined treatment for locally advanced cholangiocellular liver cancer - the case report - A. N. Polyakov; Yu. I. Patyutko; A. Yu. Syskova; K. A. Romanova; I. S. Bazin; O. N. Sergeeva; E. R. Virshke; E. S. Makarov; E. Yu. Antonova; A. A. Kirshin; D. V. Podluzhnyi (Исследования и практика в медицине)
Liver resection is the standard in the treatment of patients with the local uncomplicated intrahepatic bile duct cancer. Systemic chemotherapy is prescribed in the presence of distant metastases. Difficulties in a choice of the treatment method come up when one or several factors are revealed: the tumor spread towards the surrounding structures, multiple liver lesions, lymph nodes involvement signs. The complications presence manages treatment strategy too. The case describes the possibilities of an individual multimodal approach in a treatment strategy for the patient with locally advanced liver cholangiocarcinoma complicated by obstructive jaundice, cholangitis, cholangiogenic abscesses. The surgical approach was approved as the main one. Methods of interventional radiology, chemotherapy, radiation therapy were applied when necessary. The mentioned above treatment strategy allowed us to achieve good results in this difficult clinical case. The patient is alive for more than four years from the time of surgery, signs of progression are not currently defined.